If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 46n + -73 Reorder the terms: 6 = -73 + 46n Solving 6 = -73 + 46n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-46n' to each side of the equation. 6 + -46n = -73 + 46n + -46n Combine like terms: 46n + -46n = 0 6 + -46n = -73 + 0 6 + -46n = -73 Add '-6' to each side of the equation. 6 + -6 + -46n = -73 + -6 Combine like terms: 6 + -6 = 0 0 + -46n = -73 + -6 -46n = -73 + -6 Combine like terms: -73 + -6 = -79 -46n = -79 Divide each side by '-46'. n = 1.717391304 Simplifying n = 1.717391304
| 3-14=-9n+47 | | 6p+9=3p | | -k=22 | | r-10+22=-5 | | 2(x-6)=3x-216 | | 6=73-46 | | 5-5c=4c | | 8d=5d | | y^2+7y-6=0 | | 2÷3x=2/9 | | 73=46-6 | | 8n+4=7n-11 | | 6-4c=2c | | 4(c+7)=5c-1 | | y+7y-6=0 | | 6+4c=6c | | 5(12-3p)=15o+60 | | 45+60+68+100=180 | | 48=45 | | 5+2c=3c | | 8n+10=3n | | 4266.666667= | | (y+7)y=6 | | -28x-4= | | k^2+9k+4=0 | | 4(c+7)=5c-7 | | 2(m+8)-20= | | 1.5p=7.5 | | 14x-14=24+5x | | n/4-2=-3 | | 2k+10+3k=40 | | 12(x+9)=60 |